1996
DOI: 10.2466/pms.1996.83.1.307
|View full text |Cite
|
Sign up to set email alerts
|

A Validity Study of the Social Skills Rating System-Teacher Version with Disabled and Nondisabled Preschool Children

Abstract: This study examined the differences among social skills and problem behaviors of disabled (n = 22) and nondisabled (n = 27) preschoolers on Social Skills Rating System-Teacher Version. Significant differences were found between the two groups on all measures of social skills and all but one measure (internalizing problems) of problem behaviors. Also, correlations with a measure of social competence and 8 teachers' ratings strongly supported the validity of this measure of social skills for preschool children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Other studies have examined convergent validity and found moderate to high correlations between the SSIS and other social competence measures, including the Home and Community Social Behavior Scales (Merrell and Caldarella, 2002), the Vineland Adaptive Behavior Scales (Lyon et al, 1996), and the Behavior Assessment System for Children (Flanagan et al, 1996). In the present study, the Cronbach's alpha was 0.86 for cooperation, 0.68 for assertion, and 0.85 for self-control.…”
Section: Child Self-report Of Substance Use and Gang Involvementmentioning
confidence: 52%
“…Other studies have examined convergent validity and found moderate to high correlations between the SSIS and other social competence measures, including the Home and Community Social Behavior Scales (Merrell and Caldarella, 2002), the Vineland Adaptive Behavior Scales (Lyon et al, 1996), and the Behavior Assessment System for Children (Flanagan et al, 1996). In the present study, the Cronbach's alpha was 0.86 for cooperation, 0.68 for assertion, and 0.85 for self-control.…”
Section: Child Self-report Of Substance Use and Gang Involvementmentioning
confidence: 52%
“…In fact, SSRS was designed using multi-rater approach to view subjects multi-dimensionally. Validity is also supported by research, such as criterion-related validity (Bruinink et al 1984), construct validity (e.g., Matson et al 1983;Walker and McConnell 1988), factor validity (e.g., Carpenter, et al 2008), concurrent validity (e.g., Clark et al 1985), and discriminate validity (e.g., Lyon et al 1996). The SSRS has been used effectively to differentiate groups of children with differing special educational classifications (e.g., Stinnett et al 1989).…”
Section: Ssrsmentioning
confidence: 96%
“…These developmental differences in social behavior interfere with a young child's daily opportunities to learn in a variety of environments. Immediate outcomes of deficits in social skills at the preschool level can lead to poor adjustment in the educational setting (Lyon et al 1996), resulting in long-term outcomes such as delinquency, poor social functioning, substance abuse, violence towards others, and school drop-out (Lyon et al 1996;Carpenter et al 2008). Therefore, teaching appropriate social behaviors is a frequent goal of early intervention for young children with autism.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, Shahim (1999) has found high alpha coefficients (0.92) for the teacher versions. Studies examining convergent validity have moderate to high correlations among the SSRS and other social competence instruments, including the Woodcock-Johnson Scales of Independent Behavior (Merrell & Popinga, 1994), the Vineland Adaptive Behavior Scales (Lyon, Albertus, Birkinbine, & Naibi, 1996), and the Behavior Assessment System for Children (BASC) (Flanagan, Alfonso, Primavera, Povall, Higgins, 1996). Flanagan et al (1996) found a high positive and significant correlation between parent ratings on the BASC and the SSRS (r=0.58).…”
Section: Methodsmentioning
confidence: 99%